The Survival Status and Predictors of Mortality Among Stroke Patients at North West Ethiopia - Walelgn N; Abyu GY; Seyoum Y; Habtegiorgis SD; Birhanu MY (Dove Medical Press, 2021)
Nigusie Walelgn,1 Gebre Yitayih Abyu,1 Yeshaneh Seyoum,1 Samuel Derbie Habtegiorgis,2 Molla Yigzaw Birhanu2 1Department of Adult Health Nursing, College of Medicine and Health Sciences, Bahirdar University, Bahirdar, Ethiopia; 2Department of Public Health, College of Health Sciences, Debre Markos University, Debre Markos, EthiopiaCorrespondence: Molla Yigzaw Birhanu; Samuel Derbie Habtegiorgis Email mollayigzaw33@gmail.com; kasadr21@gmail.comIntroduction: Stroke is one of the commonest non-communicable disease types that has a great public health impact both in developed and developing countries. However, in Ethiopia, the long-term survival status of stroke patients is not very understood. This study aimed at assessing survival status and predictors of mortality among stroke patients at Felege Hiwot comprehensive specialized hospital from September 1, 2014, to August 31, 2019, Bahirdar, North West Ethiopia.Methods: An institutional-based retrospective cohort study was conducted using 368 registered stroke patients between September 1, 2014, and August 31, 2019. We used Kaplan-Meier together with a Log-rank test to compare the survival rate of the study participants using categorical variables and to compare covariate and both bi-variable and multivariable Cox proportional hazards regression analysis model was conducted to identify predictors of mortality among stroke patients. The association between outcome and independent variables was expressed using an adjusted hazard ratio (AHR) with a 95% confidence interval and statistical significances were declared at P-value of < 0.05.Results: Fifty-six (15.2%) of the 368 stroke patients included in the study died, and 312 (84.8%) were correctly censored. The overall survival rate was 72.2% at 51 months of follow-up with a median survival time of 0.26 months. Age greater than 65 (AHR 6.31, 95% CI 1.75- 22.74), body temperature > 7.1 degree centigrade (AHR = 7.14, 95% CI: 2.76- 18.5), potassium level below < 2 mmol/l (AHR = 2, 95% CI: 1.9- 23.53) and creatinine level > 1.2 mg/dl (AHR = 7.85, 95% CI: 2.7- 22.6) were predictive predictors of mortality.Conclusions: In the follow-up of 51 months, significant mortality occurred. Important predictive predictors of survival status were identified. Interventions should be focused on health education and awareness creation of the community for the early management of stroke.Keywords: stroke, survival status, predictors, mortality, Ethiopia